THE IMPORTANCE OF USING THE LAWS OF DRAWING IN TEACHING TECHNOLOGY - Avezov Bazarbay Dosnazarovich (Web of Journals Publishing, 2025)
Integrating drawing principles into technology education offers a unique approach to developing students’ creativity, problem-solving skills, and visual communication. This article explores the importance of using drawing techniques and concepts in teaching technology subjects, highlighting their role in fostering innovation, design thinking, and effective communication in a technologically driven world.
Keywords: Drawing principles, technology education, creativity, design thinking, visual communication, spatial awareness, hands-on learning.